2015
DOI: 10.1039/c5nj00364d
|View full text |Cite
|
Sign up to set email alerts
|

Development of halogen-free flame retardant phosphazene and rice husk ash incorporated benzoxazine blended epoxy composites for microelectronic applications

Abstract: The present study is focused on the synthesis and characterization of flame retardant amine-terminated cyclophosphazene and silane functionalized rice husk ash reinforced benzoxazine blended epoxy composites as a halogen-free flame retardant material (ATCP/FRHA/Bz-Ep). FT-IR spectroscopy, scanning electron microscopy (SEM), X-ray diffraction analysis, contact angle measurements, dielectric constant, DSC, TGA, UL-94, LOI and cone calorimetry were used to characterize the surface morphology as well as the struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 40 publications
4
23
1
1
Order By: Relevance
“…The UL 94 rating decreased to V‐1 and no rating when average curing temperature increased and, furthermore, without MI. Such an improvement was very remarkable in comparison with results reported in the literature, as shown in Figure . The increased effectiveness of EBM–LT with the addition of MI and the further effectiveness at a lower curing temperature were evidenced by the LOI increment value of 10.3 and the UL 94 V‐0 rating, which exceeded most reported composites.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The UL 94 rating decreased to V‐1 and no rating when average curing temperature increased and, furthermore, without MI. Such an improvement was very remarkable in comparison with results reported in the literature, as shown in Figure . The increased effectiveness of EBM–LT with the addition of MI and the further effectiveness at a lower curing temperature were evidenced by the LOI increment value of 10.3 and the UL 94 V‐0 rating, which exceeded most reported composites.…”
Section: Resultssupporting
confidence: 82%
“…The flame retardancy significantly improved with the addition of 20 wt % BOZ because BOZ is an intrinsic flame-retardant polymer (LOI = 30.8%, UL 94 V-1 rating) with a high char residue [CR; Figure 2 The UL 94 rating decreased to V-1 and no rating when average curing temperature increased and, furthermore, without MI. Such an improvement was very remarkable in comparison with results reported in the literature, [29][30][31][32][33][34][35][36][37] as shown in Figure 1. The increased effectiveness of EBM-LT with the addition of MI and the further effectiveness at a lower curing temperature were evidenced by the LOI increment value of 10.3 and the UL 94 V-0 rating, which exceeded most reported composites.…”
Section: Intrinsic Flame Retardancysupporting
confidence: 73%
“…2(a)) showed that only the MRHA has peaks at 602 and 1398 cm −1 which are related to the Fe-O bending and stretching vibration respectively [29,30]. Both for RHA and MRHA the peaks observed at 468, 798, 1103, 3145 cm −1 indicate the silica functional groups of C-Si-O, Si-H, Si-O-Si and -OH stretching respectively [29,31,32]. The N 2 adsorption-desorption isotherms of RHA and MRHA showed Type-IV isotherm with H3-type hysteresis (Fig.…”
Section: Characterizationmentioning
confidence: 97%
“…Furthermore, polybenzoxazines can be alloyed with various chemicals including epoxy [5][6][7], polyurethane [8], poly (imide-siloxane) [9], and bismaleimides [10,11], suppressing the inherent brittleness of polybenzoxazines and meeting the requirement of numerous applications with tailor-made properties. Promising applications of polybenzoxazines, their copolymers, and their composites have been demonstrated, including coating [12][13][14], proton conductive porous substrate [15], optical probe [16], bipolar plates in fuel cell [17], superinsulating materials for space applications [18], shape memory polymer [19], halogen-free flame retardant material [20], porous carbon anode [21], and self-healing polymers [22]. Even though thermal, mechanical, and electrical properties of polybenzoxazines have been widely explored and well-documented, their optical properties have not been thoroughly investigated and utilized.…”
Section: Introductionmentioning
confidence: 99%